An analysis of leg techniques in karate - Mudric, R.; Mudric, M.; Rankovic, V. (Sport Science & Practice, 2015)
Karate is today practiced in three forms: as a sports discipline, as a skill of self-defense and in the form of recreation and health. Regardless of the forms of practice, their place and roles, the leg techniques which are executed are very significant. Today karate is primarily a modern sports event in which strikes dominate and where leg techniques influence the scoring system (points made by the leg strikes and kicks are larger than those made by the arms). The paper has carried out an analysis of leg techniques which are presented from several aspects, as well as from methodical aspects with short methodological instructions which are significant in training. Also, there is a short analysis of the muscle structure, with a review of all the significant and relevant muscle groups which take part in the strikes. Also, the technical elements which are significant in executing and applying the leg techniques are defined. The techniques are presented as structural elements of the assault itself, with time dimensions and the processes describing them. This significant work segment affirms the scientific and research approach to the issue of karate, as well as martial arts in general and it is presented with the results of research in this area. The techniques are also illustrated with adequate pictures - drawings, diagrams and accompanying tables.